The guideline for customising incremental housing based on two Chilean case studies - Marinovic, Goran Ivo (Journal of Architecture and Urbanism, 2020)
Incremental housing, supported by governmental funding, denotes a solution for low-income households where they can gradually customise their dwelling. The Chilean government officials and architects proposed phases of construction which fell short of addressing the households’ capabilities and motivation to finalise their units. Hereof, this article looks at two incremental housing projects: Lo Espejo condominium (2007) and Las Higueras (2006) in the Santiago Metropolitan Region, Chile, to inquire capacities of government officials and architects’ comprehensive assistance to families’ housebuilding. The hypothesis holds that the greater responsibility of government officials and architects engaged with incremental housing will enhance motivation of low-income families to customise their house by self-building practice. Arguing for the importance of the self-building the author proposed the guideline for customising houses that comprises four phases: introducing the incremental construction design idea, discussing with families the possibilities for completing houses, connecting households’ construction plans with their financial resources, and presenting the customisation design template. This guideline structure is founded on extensive nine months fieldwork in the Santiago Metropolitan Region, carried out in close collaboration with low-income households from two neighbourhoods, the Ministry of Housing and Urbanism of Chile, the Architectural Office Elemental, and “Gubbins Arquitectos.”